Scherrer grain-size analysis adapted to grazing-incidence scattering with area detectors - Smilgies, Detlef-M. (Journal of applied crystallography, 2009)
Ever since its formulation, the Scherrer formula has been the workhorse for quantifying finite size effects in X‐ray scattering. Various aspects of Scherrer‐type grain‐size analysis are discussed with regard to the characterization of thin films with grazing‐incidence scattering methods utilizing area detectors. After a brief review of the basic features of Scherrer analysis, a description of resolution‐limiting factors in grazing‐incidence scattering geometry is provided. As an application, the CHESS D1 beamline is characterized for typical scattering modes covering length scales from the molecular scale to the nanoscale.